Analisis Reduksi Debit Banjir Sistem Drainase Kali Kencing Di Kabupaten Kudus - Istianah Istianah; Fitria Maya Lestari; Bambang Tutuko (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2026)
Flooding is a common issue affecting various regions in Indonesia, particularly in densely populated urban areas. High rainfall intensity leading to river overflow, dense residential settlements, and inadequate drainage systems and environmental conditions are key factors contributing to flood disasters. This study aims to analyze the drainage capacity of the Kali Kencing channel, evaluate the existing drainage system, and assess the potential flood reduction through the implementation of a polder system within the Kali Kencing drainage network. A qualitative research method is applied, incorporating hydrological and hydraulic analyses, which are further simulated to model the relationship between retention pond storage and optimal pump capacity. The analysis reveals that the current drainage capacity of Kali Kencing is insufficient to convey the existing discharge, resulting in runoff that affects residential areas and agricultural fields. The existing system only includes a small long-storage facility and lacks adequate pumping capacity. Therefore, a retention pond covering 4.5 hectares is proposed to temporarily store excess water during elevated water levels in the Wulan River. Simulation results indicate that the retention pond can reduce peak flood discharge from 65.10 m³/s to 36.00 m³/s, achieving a 55% reduction. Additionally, the installation of two flood pumps with a capacity of 5 m³/s each, along with one pump of 1 m³/s for low-flow operation, is recommended to enhance system performance.